2012
DOI: 10.1111/j.1476-5381.2012.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

The omega‐3 polyunsaturated fatty acid eicosapentaenoic acid inhibits mouse MC‐26 colorectal cancer cell liver metastasis via inhibition of PGE2‐dependent cell motility

Abstract: BACKGROUND AND PURPOSEThe omega-3 polyunsaturated fatty acid (PUFA) eicosapentaenoic acid (EPA) has antineoplastic activity at early stages of colorectal carcinogenesis, relevant to chemoprevention of colorectal cancer (CRC). We tested the hypothesis that EPA also has anti-CRC activity at later stages of colorectal carcinogenesis, relevant to treatment of metastatic CRC, via modulation of E-type PG synthesis. EXPERIMENTAL APPROACHA BALB/c mouse model, in which intrasplenic injection of syngeneic MC-26 mouse CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 34 publications
5
39
1
Order By: Relevance
“…Our findings are in line with other studies that have also reported the role of ROCK in regulating Cox-2 expression downstream of another GPCR, proteinaseactivated receptor-2 (Hirota et al, 2012). Current evidence indicates that Cox-2-PGE 2 signaling stimulates colon cancer cell migration through activation of its cognate prostaglandin (Buchanan et al, 2003;Hawcroft et al, 2012). Overall our data suggests that the modest defect in cancer cell motility observed with celecoxib treatment indicates that Cox-2-PGE 2 signaling is not the main regulator of GRPstimulated colon cancer cell migration, and most probably it is predominantly controlled by PRG-RhoA-ROCK pathway directly regulating actinomyosin contractile machinery.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are in line with other studies that have also reported the role of ROCK in regulating Cox-2 expression downstream of another GPCR, proteinaseactivated receptor-2 (Hirota et al, 2012). Current evidence indicates that Cox-2-PGE 2 signaling stimulates colon cancer cell migration through activation of its cognate prostaglandin (Buchanan et al, 2003;Hawcroft et al, 2012). Overall our data suggests that the modest defect in cancer cell motility observed with celecoxib treatment indicates that Cox-2-PGE 2 signaling is not the main regulator of GRPstimulated colon cancer cell migration, and most probably it is predominantly controlled by PRG-RhoA-ROCK pathway directly regulating actinomyosin contractile machinery.…”
Section: Discussionsupporting
confidence: 82%
“…Evidence from in vitro and in vivo studies have shown that Cox-2-PGE 2 signaling increases colon cancer cell migration and invasion (Buchanan et al, 2003;Hawcroft et al, 2012;Ninomiya et al, 2012). Therefore, we wanted to identify the contribution of Cox-2-PGE 2 signaling to overall GRP-stimulated colon cancer cell migration.…”
Section: Pdz-rhogef Drives Colon Cancer Cell Migrationmentioning
confidence: 99%
“…LC-ESI-MS/MS analysis of hydrolysed lipid extracts from liver samples revealed a significant increase in the % amount of EPA, DPA and DHA, as well as a significant reduction in the relative amount of AA, LA and OA in the liver of mice fed the diet containing 5% (w/w) EPA (figure 5, p<0.05). These FA values are similar to those obtained by GC-MS measurement in a previously published EPA treatment experiment [18]. Therefore, the LC-ESI-MS/MS method can detect omega-3 PUFA changes in mouse tissue following exogenous administration of EPA.…”
Section: Measurement Of Omega-3 Pufa Incorporation In Mouse Liversupporting
confidence: 87%
“…The relative FA content of MC38 cells exposed to EPA-FFA was measured by GC-MS, as previously described [18,19]. In brief samples, into which internal standard was added (Heneicosanoic acid, 2.5 µg/sample), were homogenized in 0.5 ml saline, then purified by liquid/liquid extraction ( Choroform: Methanol 2:1 vol/vol, 3+2 ml, 0.5% di butylated hydroxytoluene [BHT]) twice.…”
Section: Gc-ms: Extraction and Analysismentioning
confidence: 99%
“…Dietary fish oil has been demonstrated to reduce CRC cell tumour growth 5. We recently tested the effect of EPA-FFA on MC-26 mouse CRC cell liver metastasis (CRCLM) in BALB/c mice 7. We demonstrated that EPA-FFA treatment was associated with reduced liver tumour burden 7…”
Section: Introductionmentioning
confidence: 99%